César Vallejo: Revocation of Death. (Presence of a Motive Until its Origin in The Black Heralds) - Lespada, Gustavo (2019)
Death is an omnipresent subject in Vallejo’s poetry. In the so-called Human Poems there are many direct references and even a teleological feature is attributed to him: «To have been born to live from our death!». In his moving poems about the Spanish Civil War, Spain, Take This Cup From Me, «kill death» will be the Peruvian poet’s oxymoronic urge against the crimes of fascism. On this occasion we intend to trace the thread of the deal with death from those posthumously published poems to The Black Heralds (1919), to observe in this first poems —in a kind of journey to the origin— the nuances, the changes, but also the advances of an aesthetic identity, the first social or community pronouncements about death and its miseries, that is, the constancy and productivity of this motive in one of the most singular poetics of all time.